Labor Market Tightness in Advanced Economies - Duval, Romain (Staff Discussion Notes; Staff Discussion Notes, 2022)
Two years after the onset of the COVID-19 pandemic, a puzzle has emerged in several advanced economies: unfilled job vacancies have increased sharply even though employment has yet to fully recover. This note sheds light on three contributing factors, namely barriers to returning to work, changing worker preferences away from certain types of jobs, and sectoral and occupational job mismatch. The note also assesses the impact of labor market tightness on wage growth, showing that it has been large for low-pay jobs but milder overall. Bringing disadvantaged groups of workers into the labor force, including by controlling the pandemic itself, would ease labor market pressures while amplifying the recovery and making it more inclusive.